Cumhuriyet dönemi Türk edebiyatı - Enginün, İnci (Dergâh Yayınları, 2001)
Turkish literature; 20th century; history and criticism.
Literaturverz. S. [408] - 410
Keywords: Turkish literature; Literatur; Türkisch